Distribution and origin of natural gas leakage in the Colorado Basin, offshore Argentina 2 Margin, South America: seismic interpretation and 3D basin modelling - Rodríguez, Jorge F; Vallejo, E; Anka, Zahie; Marchal, Denis; Loegering, M. J; Di Primio, R (Geologica acta, 2014)
The detailed analysis of a dense 2D seismic reflection dataset and data from 8 exploration wells, allowed us to identify, map out and characterize possible indications of past and present-day hydrocarbon leakage (i.e. gas chimneys, gas pockets, and seafloor mounds and pockmarks) on the continental shelf and slope of the Colorado Basin, offshore Argentina, where Permian, Jurassic and Early Cretaceous source rocks are potentially present and may be currently mature. Identified gas leakage features, developed both in the syn-rift and post-rift successions, were also analysed in relation to the structural the stratigraphic elements of the basin. A family of seabed pockmarks, located close to an array of submarine channels, was identified on the distal slope of the basin. These pockmarks are overlying a series of sub-vertical to vertical seismic chimneys in the subsurface. A calibrated basin-wide 3D petroleum system model comprising generation and migration of hydrocarbons was carried out and compared with the observations from the seismic analysis. Preliminary results from this model indicate that although synrift and early Cretaceous source rock (SR) intervals may be depleted in the central areas of the basin, an active kitchen from the Aptian SR may be present below the slope areas. Hydrocarbon migration pathways predicted by the 3D model (Hybrid method) coincide with the interpreted seismic chimneys underlying the observed seabed slope pockmarks. Hence, our results indicate that thermogenic gas may be currently generated in the distal slope of the basin from mature early post-rift source rocks within the Early Cretaceous (Aptian) sequences and migrates vertically, due to seal failure, through the stratigraphic column. This migrating thermogenic gas is feeding the seafloor pockmarks identified in the distal slope of the basin, although up-dip lateral migration along stratigraphic layers to the more proximal slope areas cannot be ruled out. The present work represents the first published study integrating detailed seismic analysis and 3D basin modelling linking observed gas-leakage indicators and associated seepage pathways, to their relative abundance, distribution and feeding systems offshore Argentina’s continental margin.